Immunization status of children in Nepal and associated factors, 2016. Issue 40 (24th September 2021) - Patel, Pooja N.; Hada, Manila; Carlson, Bradley F.; Boulton, Matthew L.
Highlights: Childhood immunization is essential in reducing morbidity and mortality. Almost 22% of children aged 12–23 months were not fully immunized, leaving them at increased risk. Higher level of maternal education was associated with increased odds of full immunization. The retention of immunization cards was associated with increased odds of full immunization. Institutional births (public and private) were associated with increased odds of full immunization. Abstract: Background: Nepal has made substantial improvements in childhood immunization uptake. However, vaccination levels are still below the country-specific Sustainable Development Goal target of 94.8% coverage by 2025 for children aged 12–23 months who received all immunizations recommended in the national immunization schedule by their first birthday. A better understanding of the predictors of full immunization can inform successful programmatic interventions to improve coverage while also guiding resource allocation to ensure all children are fully vaccinated. This study estimates childhood immunization coverage in Nepal and characterizes the association between immunization status and various sociodemographic predictors. Methods: Data from the 2016 Nepal Demographic and Health Survey were used to examine the immunization status of children aged 12–23 months. Immunization status was categorized as fully immunized (receiving all recommended doses), under-immunized (receiving at least one, but not all, recommended doses), and un-immunized (not receiving any doses of any vaccine). Associations between full and under-immunization and potential sociodemographic predictors were assessed using logistic regression. Results: Among 976 children, 78.2% were fully immunized, 21% were under-immunized, and 0.8% were un-immunized. Retention of an immunization card was significantly associated with full immunization status. Mothers who had completed a formal education above secondary school and mothers who were working at time of interview had increased odds of full immunization. Birthing in an institutional setting was also associated with higher odds of full immunization. Conclusions: Overall, immunization coverage in Nepal is relatively high, although it varies by dose and sociodemographic factors. Almost 25% of Nepalese children were not fully immunized, leaving them at increased risk for vaccine-preventable disease related morbidity and mortality. Nepal must continue focused efforts to reach every child and minimize the equity gap; programs may focus on advocating for the use of immunization cards, education and empowerment for girls, and delivery in institutional settings.